2015
DOI: 10.1650/condor-14-200.1
|View full text |Cite
|
Sign up to set email alerts
|

Geolocators on Golden-winged Warblers do not affect migratory ecology

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 19 publications
2
51
0
Order By: Relevance
“…There was no indication of an interaction between attachment method and stalk length that might indicate that snagging in vegetation was a problem. There is, of course, a trade‐off between the utility of a geolocator without a light stalk because light records are less accurate when the light sensor (located at the end of a light stalk for stalked geolocators) is covered with feathers, and so fewer reliable positions may be obtained (but see Peterson et al where the presence of stalks made no difference to data quality).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no indication of an interaction between attachment method and stalk length that might indicate that snagging in vegetation was a problem. There is, of course, a trade‐off between the utility of a geolocator without a light stalk because light records are less accurate when the light sensor (located at the end of a light stalk for stalked geolocators) is covered with feathers, and so fewer reliable positions may be obtained (but see Peterson et al where the presence of stalks made no difference to data quality).…”
Section: Discussionmentioning
confidence: 99%
“…Small birds (< 15 g) present the current limit for field attachment of tags because battery limitations mean that tags are relatively large and at the 3–5% of body weight limit that is widely regarded as the threshold for significant effects (Cochran , Caccamise and Hedin , Kenward ). The use of geolocators on small passerines has so far produced equivocal results with respect to whether their use impacts fitness (Bridge et al , Fairhurst et al , Peterson et al ) or substantially reduces survival rate (Costantini and Moller , Gomez et al ), although a meta‐analysis concluded that deleterious effects are widespread (Barron et al ). A key issue is that the majority of geolocator studies do not have a formal control group, nor do they adopt an experimental approach to measure variation in effects due to tag design.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the ethical, conservation and scientific implications, the deployment of such devices should therefore be associated to the assessment of their impact on birds (e.g. Arlt et al 2013;Scandolara et al 2014;Peterson et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Peterson et al. () found that geolocators had no effect on the migratory behavior of male Golden‐winged Warblers (Peterson et al. ).…”
Section: Methodsmentioning
confidence: 99%